The Influence of Cooperative Learning Model Type of Group Investigation (Gi) Assistant Media Counting Funny on Understanding Multiplication Concept (Research on Class III Students of MI Muhammadiyah Sawangan) - Catur Wulandari (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of the group investigation (GI) cooperativelearning model with the help of funnel counting media on the understanding ofmultiplication concepts in third grade students of MI Muhammadiyah Sawangan. Thisresearch is a type of pre-experimental research with one group pretest-posttest model. Theresearch subjects were all third grade students of MI Muhammadiyah Sawangan with asaturated sampling model. The sample taken as many as 16 students. The method of datacollection was carried out using an objective test in the form of multiple choice. Test thevalidity of the test instrument using the product moment while the reliability test usingCronbach alpha. The analysis prerequisite test used the normality test. Data analysis usedpaired sample t-test paramatretic test technique with the help of SPSS version 23.00 forwindows program. The results of this study indicate that the group investigation (GI)cooperative learning model with the help of funnel counting media has an effect onunderstanding the concept of multiplication. This is evidenced by The results of the pairedsample t-test analysis showed that the significance value was 0.000, which means less than0.05 (sig 0.000 <0.05). The calculation of the average score of the objective posttest objectivetest of 74.00 which is higher than the average value of the pretest objective test of 52.6.